Singkong-In Untuk Kewirausahaan Berkelanjutan: Meningkatkan Pendapatan Dan Kemandirian Ekonomi Masyarakat Rabadompu Barat - haryanti, intisari; Puji Muniarty; Mawar Hidayanti; Ovriyadin; Marsya Humairah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2025)
This study aims to develop cassava potential as a local-based entrepreneurial product in Rabdompu Barat, Kota Bima. Cassava is an important commodity that is still largely utilized in traditional ways without optimal added value. Using a qualitative research method combined with a Research and Development (R&D) approach, data collection, training, and the development of an innovative cassava-based business model were carried out. The results indicate that developing cassava products such as chips with packaging and marketing innovations can significantly improve entrepreneurial skills and community income. Training and mentoring encourage the community to transform from merely farmers into independent entrepreneurs who can manage cassava products productively and sustainably. This study contributes significantly to strengthening the local economy by increasing the added value of cassava commodities and empowering the Rabadompu Barat community. Keywords:Cassava-in, Sustainable Entrepreneurship, Income, Economic Independence